2017
DOI: 10.3389/fnana.2017.00082
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Functional Neuroanatomy of the Lumbar Spinal Cord in Effect of Epidural Stimulation

Abstract: In this study, the neuroanatomy of the swine lumbar spinal cord, particularly the spatial orientation of dorsal roots was correlated to the anatomical landmarks of the lumbar spine and to the magnitude of motor evoked potentials during epidural electrical stimulation (EES). We found that the proximity of the stimulating electrode to the dorsal roots entry zone across spinal segments was a critical factor to evoke higher peak-to-peak motor responses. Positioning the electrode close to the dorsal roots produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 57 publications
(100 reference statements)
2
47
0
Order By: Relevance
“…In turn, the physiological spread of the stimulation-induced excitatory drive due to fibers' collaterals defines the upper-bounds of the potential for spatial specificity. Therefore, the optimization of spinal implants requires integrating not only the dimensions of spinal segments but also the path of the dorsal roots in the design of electrode locations 8,20,39 (Fig. 2).…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…In turn, the physiological spread of the stimulation-induced excitatory drive due to fibers' collaterals defines the upper-bounds of the potential for spatial specificity. Therefore, the optimization of spinal implants requires integrating not only the dimensions of spinal segments but also the path of the dorsal roots in the design of electrode locations 8,20,39 (Fig. 2).…”
Section: Anatomical Considerationsmentioning
confidence: 99%
“…Electrophysiological tests were performed under anesthesia on experimental pigs before the injury, at 15 min, and at 6 and 22 weeks after SCI. The M-and H-waves (pigs only have M-response) from the tibialis anterior muscle in pigs and the gastrocnemius muscle in rats were recorded in response to stimulation of the sciatic nerve [37,38].…”
Section: Electrophysiological Studiesmentioning
confidence: 99%
“…Multiple computational (9-11) and animal studies (13,25) demonstrated that dorsal roots and dorsal columns are the main target for EES, which emphasizes the importance of electrodes location in relation to the main target structures (9)(10)(11)(12). It has been reported that electrical stimulation applied at DREZ provides significantly higher motor evoked responses compared to other electrodes location on dura mater (3,13). Orientation of electrical field along the fibers of target structures is another key factor in effect of EES (8).…”
Section: Discussionmentioning
confidence: 99%